PENINGKATAN KESELAMATAN DAN KESEHATAN KERJA MENGUNAKAN METODE FAULT TREE ANALYSIS DAN 5W1H PADA PT. HOMEWARE INTERNATIONAL INDONESIA (Universitas Esa Unggul, 2017)
PT. Homeware International Indonesia has producing furniture and household accessories made from rattan or wood. The productshaveÂ produced include table tops, baskets, home accessories, light furniture, and ceramics. The number of accidents and occupational health of the company is still relative highly. The purpose of this research is to identify, analyze and provide suggestions for improvements, and recommendations for actions to minimize the causes of work accidents. The analysis of the problem from the Pareto Chart shows that burns are the main type of accident.Through analysis using Fishbone Diagrams, Matrix Diagrams, Fault Tree Analysis, to proposed improvements with 5W + IH, it were concluded that the causes that have the largest priority scale are humans, machines, and the environment with the root of the problem that occurs in burn accidents including pressureÂ from supervisors, chasing targets, neglect, irregular machine maintenance schedule, lack of air ventilation and maintenance of exaust. Proposed preventive actions and recommendations for actions to prevent problems that occur, namely understanding the regulations, making a good production schedule, understanding the SOP, checking the temperature of breaking downperiodically, making maintenance schedules, carrying out exaust maintenance and adding air ventilation.Â Keywords: occupational health and safety, pareto chart , diagrammatrix, fault tree analysis